The Role of Radiotherapy in Extramammary Paget Disease: A Systematic Review. Issue 4 (1st May 2018) - Tagliaferri, L.; Casà, C.; Macchia, G.; Pesce, A.; Garganese, G.; Gui, B.; Perotti, G.; Gentileschi, S.; Inzani, F.; Autorino, R.; Cammelli, S.; Morganti, A.G.; et al.
Abstract : Objective/Purpose: Extramammary Paget disease (EMPD) is a rare neoplasm of the skin generally affecting the anogenital area. Because of the low-frequency of the disease, no specific guidelines about the treatment strategy are available. Surgery is the recommended therapy for resectable and localized disease, but several other local treatments have been reported such as radiotherapy (RT). Most articles report small retrospective studies, referring to patients treated decades ago with large heterogeneity in terms of RT dose and technique. The aim of this study was to systematically review the main experiences in RT for the treatment of EMPD in the past 30 years. Materials and Methods: A systematic search of the bibliographic databases PubMed and Scopus from January 1986 to January 2017 was performed including studies published in English, Italian, Spanish, French, and German language. Results: According to the search strategy, 19 full-text articles, published from 1991 to 2015, fulfilled inclusion criteria and were included in the final review. All articles were retrospective analyses with no randomized controlled trials. These studies evaluated 195 EMPD patients treated with RT, delivered in several settings. A large variability in terms of RT doses, fractionation, clinical setting, and techniques was found. Radiotherapy was administered as definitive treatment for primary or recurrent disease after surgery in 18 studies with doses ranging from 30 to 80.2 Gy delivered in 3 to 43 fractions. Radiotherapy was administered as postoperative adjuvant treatment in 9 articles with doses ranging between 32 and 64.8 Gy in 20 to 30 fractions. Two studies reported the RT use in preoperative neoadjuvant setting with doses ranging between 40 and 43.30 Gy, and 2 experiences reported the RT treatment for in situ EMPD, using 39.6 to 40 Gy. Adverse events were reported in almost all but 2 articles and were grade 2 or lower. The 18 studies evaluating RT as definitive treatment for primary or recurrent disease after surgery reported a complete response rate ranging from 50% to 100%, with a variable rate of local relapse or persistent disease ranging from 0% to 80% of cases. The 9 studies evaluating RT as postoperative adjuvant treatment reported a local relapse or persistent disease rate of 0% to 62.5%. A dose-response relationship was reported suggesting doses greater than or equal to 60 Gy for gross tumor volume treatment. Local control, disease-free survival, and overall survival at 12, 20, and 60 months have been retrieved for available data, respectively. In patients with EMPD and concurrent underlying internal malignancy, the prognosis was often worsened by the latter. In this setting, literature analysis showed a potential RT palliative role for symptoms control or local control maintenance. Derma tumor invasion greater than 1 mm and lymph node metastases were reported to be important prognostic factors for distant metastases or death. Conclusions: To date, literature highlights the role of RT in the management of EMPD, but with low level of evidences.